European Union lesbian, gay, bisexual and transgender survey, 2012: special licence access (UK Data Service, 2022)
The EU Lesbian, Gay, Bisexual and Transgender Survey (EU LGBT) was conducted by the European Union Agency for Fundamental Rights (FRA). It is the first ever EU-wide online survey to establish an overview concerning the lives of lesbian, gay, bisexual and trans people (18 years or older) and their experiences with regard to fundamental rights in the 28 EU Member States. Up until now, there has been very little comparable data collected across the EU about the everyday experiences of LGBT people with respect to discrimination, and lot of the available information is limited to occasional news reports and court judgements. As the first EU-wide survey of its kind, the results support the development of equal treatment policies for LGBT people in the European Union and set the agenda for years to come. Based on the survey results, national and European policy makers, as well as non-governmental organisations, are able to better target their advocacy strategies and activities to support LGBT communities to live and express themselves freely in a non-discriminatory environment. The survey was completely anonymous (no additional data on the participants and their sessions were logged in any way). The survey data collection operated by Gallup Europe, a professional survey and consultancy firm. In order to ensure that the survey delivers evidence needed for policy making, the EU LGBT Survey counted on the participation of a large and diverse group of lesbian, gay, bisexual and trans people from each country. Hence, it was vitally important for the success of the survey that FRA and Gallup worked together with civil society organisations to reach a wide audience and raise awareness concerning the survey, including participants emailing the survey, sharing it through social media or simply inviting LGBT friends to take part.